Improving The Gross Motor Skills Of Mentally Retarded Children Through Rhythmic Brain Gym Activities - Baqiyudin, Galang; Nurhasan, Nurhasan; Suroto, Suroto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aims to identify and describe the influence of Brain Gym or brain exercises to increase gross motor skills and fine motor mental reterdation category were aged 4 years to 6 years. In this study, the sample were students in kindergarten SLB Muhammadiyah Jombang. This study was conducted in 10 meetings for each child. Each child will be given the treatment in the form of brain exercise, starting from the lateral dimension, focusing dimension and the dimension of convergence. Tests performed every time the student has finished the movement brain gymnastics. This is done so that the results of tests that are obtained more accurately. Mental reterdation characteristics that have limitations in considering would negatively affect the test results. Tests for gross motor movement and fine motor movement using DDST test format. DDST contains procedures for conducting tests and evaluation of test results. For the tests of gross motor movement and fine motor movement there are three assessment criteria, namely failed, refused and passed. At the beginning of the meeting five tests carried out many items in the category of students failed and refused. This is caused by the adaptation of students in recognizing the new environment and the movement of brain exercises that they have never done before. At the end of the five meetings that the number of test items in the category refuse and fail to decline, it is because the students have started to adapt and understand instructions, instructions were given to them. Overall improvement of the results of tests on five initial meeting and five final meeting for categories of pass is 33.8%. Based on this research exercise influence Brain Gym on the development of gross motor movement and fine motor skills of children with intellectual challenges, it can be argued conclusions in this study are: Gymnastics Therapy Brain (Brain Gym) have an influence on the development of gross motor movement and fine motor movement for mental reterdation midle category were aged 4 years to 6 years.